Analyzing language features of construction contracts from the multi-dimensional perspective - Yuzhu, Bian; Noor Mala Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2024)
In recent years, China’s active participation in the international construction market has led to a greater demand for the comprehensive demystification of construction contracts from the language perspective. Nevertheless, scarcity can be felt concerning that perspective. This study aims to explore language features via the multi-dimensional approach proposed by Biber. A corpus-driven method was adopted on the basis of five real construction contracts. The salient language features were uncovered statistically by adopting the Multi-dimensional Analysis Tagger (MAT), and a series of visualized results displaying lexico-grammatical features and general genre features of construction contracts from different dimensions were also output. The results revealed that nouns and normalization were densely employed in construction contracts. Meanwhile, language variables like phrasal coordination, predicative modals, passive voice, and suasive verbs were excessively employed. The results also uncovered that adverbs and be as the main verb were counted as underused. As to the general genre features, the results suggested that the contracts were written documents with informational, non-narrative, context-independent, self-assertive, and abstract features. Those features stem from the communicative purposes of construction contracts, rendering construction contracts the formal style, explicit communicative purposes, objective stance, and authoritative position. Though with limited language features, we can still obtain an insight into the interpretation and teaching of construction contracts.